Factores de desarrollo del proceso de internacionalización de las empresas peruanas de explosivos - Salvador Diaz, Pilar Isabel (2018)
The present investigation analyzes the process of internationalization of the Peruvian explosives companies Exsa and Famesa. Being a non-traditional industry, it is interesting to discover how both companies have managed to develop within it and internationalize. With that purpose, two development factors were proposed: the regional approach and strategic management, which are derived from the theories of internationalization approached in the theoretical framework and qualitative research. The study period covers the years 2007 - 2016. The first chapter refers to the theoretical framework, which presents information of the industry, related prior studies and theories from the economic perspective, process and networks. In the second chapter, the problem to be approached is presented, the hypothesis, the general objective and the specific objectives. In the third chapter, the work methodology is exposed, covering the type, design and method of the research, as well as its limitations. In the fourth and fifth chapter the development and analysis of the research is carried out, where information of both companies and the explosives industry is exposed, giving way to the analysis of their internationalization processes and the approach of two factors of development, which are derived from theories and qualitative research. In the sixth and last chapter the conclusions reached are presented, the specific objectives and the general objective are reached, and the recommendations are stated.